Efektifitas Pemanfaatan Rumah Isolasi Coronavirus Disease (Covid-19) di Desa Markanding Kabupaten Muaro Jambi - Masriyani Masriyani; Islah Islah (Universitas Batanghari Jambi, 2023)
This study aims to determine and analyze the effectiveness of the use of the Covid-19 isolation house in the village of Markanding, Muaro Jambi Regency. The research method is empirical juridical. The results of his research are in the form of a description of the effectiveness of the use of isolation houses, in which the program is budgeted for through the village budget which turns out to be not utilized or is ineffective to the fullest and even seems in vain. The obstacles encountered in the study were the awareness of the people who were exposed to Covid-19 which did not support where they were closed so they did not notify the officers of the Covid-19 handling post who had their last contact, and the self-isolation treatment stage where some people did not all carry out independent isolation and not also taking advantage of the available isolation houses, besides that it is also related to inadequate infrastructure. So it can be concluded that the isolation house is said to be ineffective.